Histoarchitectural Changes in the Stromal Tissue of Udder of Small Ruminants - Senthilkumar, S. (Indian Journal of Veterinary Anatomy, 2020)
In both ewes and she-goats, the mammary gland was covered from without inwards by skin and fibroelastic capsule. Udder skin made up of epidermis and dermis. Epidermis lined by stratified squamous keratinised epithelium. Dermis composed of dense irregular connective tissue with numerous sweat glands, sebaceous glands, hair follicles, and nerve fibres. Statistically no difference was observed in capsule thickness between lactating and non-lactating groups in Madras Red ewes and Boer local she-goats. The amount of stromal tissue varied between lactating and non-lactating animals. It was found to be more in non-lactating animals. The interalveolar septae were composed of collagen, elastic and reticular fibres, fibroblast, smooth muscle fibres, fat cells and nerve fibre bundles. Bundles of thick, dense connective tissue made of collagen, elastic and reticular fibres constituted the interlobar septae. Highly significant difference was observed in the thickness of interalveolar and interlobular septa between lactating and non-lactating groups in both ewes and she-goats.